Integrated water resources management as water management policy in Brazil - Silva, Mayane Bento; Herreros, Mário Miguel Amin Garcia; Borges, Fabricio Quadros (Revista de Administração da UFSM, 2017)
Due to the importance of water for life and development, several international debates focused on the construction of strategies to mitigate the risk of water scarcity, resulting in a new management paradigm, called Integrated Water Resources Management (IWRM). Therefore, this study analyzes how Brazil is managing its water resources, in order to evaluate its proximity to the IWRM model, using a qualitative, exploratory research based on secondary, bibliographic and documentary sources. The results show that Brazil has advanced in terms of law, water management and use and has been progressively integrated into the IWRM model, but it still needs to enable actions that are supported in a more participatory and decentralized environment to extend homogeneously Water management mechanisms, in order to reach regions such as those in the Amazon basin.